Sosialisasi Pentingnya Gizi Seimbang Dan Pola Asuh Guna Meningkatkan Kualitas Gizi Menuju Generasi Unggul - Nasrulloh, Muhammad Farid; Zidan, Zainuddin Azizun; Khuzaini, Nanang; Zuhriawan, Muhammad Qoyum; Hidayatulloh, Faisol; Khotimah, Khusnul (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2025)
Education is the foundation that connects knowledge about nutrition and parenting with concrete actions in everyday life. With quality education, we can create a healthy, intelligent generation that is better able to face future challenges. Based on the results of observations in the Nglele village community, especially with one of the integrated health post (Posyandu) cadres in Nglele Village, there is a problem of stunting in Nglele Village, due to several factors, one of which is the lack of insight into the importance of maintaining a balanced diet for the baby. The purpose of this socialization of the importance of balanced nutrition and parenting is to improve the quality of nutrition towards a superior generation in Nglele Village. The methods used in this service are socialization and mentoring methods. Based on the results and discussions of the implementation of community service activities with the socialization of